Balance of Payments Manual, Sixth Edition. (Manuals and Guides; 2009, 2012)
The sixth edition of the Balance of Payments and International Investment Position Manual presents revised and updated standards for concepts, definitions, and classifications for international accounts statistics. These standards are used globally to compile comprehensive and comparable data. The sixth edition is the latest in a series that the IMF began in 1948. It is the result of widespread consultation and provides elaboration and clarification requested by users. In addition, it focuses on developments such as globalization, financial market innovation, and increasing interest in balance sheet analysis.